How are the potential gains from economic activity transmitted to the labour factor: more employment or more wages? Evidence from the Portuguese context - Carreira, Carlos (2020)
The paper analyses the role of knowledge externalities in firms' employment and workers' wages. We test whether agglomeration economies and regional knowledge base exert a greater impact on wage growth than on employment growth, using spatial panel econometric techniques to control for unobserved spatial effects. Using a spatial panel for six Portuguese manufacturing industries, we found that regional knowledge spillovers, contrary to the theoretical assumptions, have a greater impact on employment in firms than on workers' wages. This analysis might enhance important policy debates about the effects of regional policies on employment and wages.